KOMPOSISI KIMIA DAN ALAMI 20 KEAWETAN JENIS KAYU INDONESIA DENGAN PENGUJIAN DI BAWAH NAUNGAN - Jasni; Gustan Pari; Esti Rini Satiti (BRIN Publishing, 2016)
Wood utilization for various products such as building construction, furniture and handycrafts deserves through attention to the properties such as chemical composition and durability, as those are interrelated. This paper investigates chemical composition and natural durability of 20 wood species originated from several Indonesian regions. Celluloses content was analyzed according to Norman and Jenkin methods; lignins content was tested according to SNI 14-0492 1989; and extractives content was analysed based on SNI 14-1032-1989. Testing of wood durability was conducted under the shade at Cikampek, experiment station, West Java. Durability observation was conducted in one year afterwards by assessing the percentage damage of wood samples caused by wood-destroying organisms. Results show that jaha wood (Terminalia arborea K.et.V.) exhibited the highest cellulose content (61.35%), while the lowest (43.30%) at bambang lanang wood (Michelia champaca L.var.pubinervia). Mahang putih wood (Macaranga hypoleuca Muell. Arg.) contain the highest lignin (35.80%), conversely cempaka wood (Elmerrillia papuana Dandy) contain the lowest lignin (23.67%). The highest extractive content (7.87%) was found at bawang wood (Azadirachta exelsa (Jack) M. Jacobs), while the lowest content found at kandis wood (Pentaphalangium pachycarcum A.C. Smith.) with extractive content of 1.52%. Assessment on natural durability indicated that four species were categorized as durable (class II), six species as rather durable (class III), three species as not-durable (class IV), and seven species as perishable (class V).